Emergy Assessment of a Wastewater Treatment Pond System in the Lake Victoria Basin - Grönlund, Erik; Billgren, Charlotte; Tonderski, Karin S.; Raburu, Phillip O. (Journal of Environmental Accounting and Management, 2026)
As part of efforts to reduce the eutrophying load to Lake Victoria, a wastewater treatment system at one of the sugar factories in Kenya was evaluated with the ecosystem ecology method emergy accounting. As a comparison a traditional cost analysis was also performed. The analysis included the local and imported ecosystem services. After preliminary treatment the effluent was discharged into a series of 12 stabilisation ponds. The removal of COD and TSS was high, whereas phosphorus concentrations were reduced by less than 20 %. The monetary costs were dominated by operation and management cost, some of which could probably be reduced by more effective management. The local ecosystem services in emergy terms contributed only 1% (or 1,000 Em) to the treatment system. Imported ecosystem services in purchased lime contributed more to the treatment system, 22% (or 24,600 Em). Since the land costs in the area were low, land demanding treatment methods using free local ecosystem services, could be cost effective choices for wastewater management. Ecosystem ecology methods as emergy accountings can guide these choices by revealing the additional contribution of free ecosystem services. Emergy accountings seem to need further clarification regarding differences in micro-/macroeconomic views.